The Economic and Social Implications of Unemployment on The Aggregate Demand and The Labor Market In Iraq - Rajaa Khudhair Al- Rubay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Unemployment in its various forms is one of the most important economic and social problems experienced by the economies of many developing countries and developed countries alike with a difference in causes, results, and solutions. The problem is caused by many reasons, including high illiteracy, low educational and health levels. The inability of the national economy to absorb the most significant possible amount of labor because of the lack of investment in investment projects and services, high population growth, and poor productivity, Wars, and political instability, which was reflected, directly and indirectly, to confuse the economic landscape of the country. The research discussed the leading causes of unemployment and its effects on the economy and society and the development of solutions proposed to address and reduce them.